Isolation and Identification of Bacteria Producing Extracellular Protease from Port Dickson Seashore, Negeri Sembilan and Kelana Jaya Lake, Selangor - Yahya, Abdullah; Samian, Mohammed Razip; Baharuddin, Aida (Asian Journal of Biological and Life Sciences, 2017)
This study was conducted to isolate extracellular protease producing bacteria from the Port Dickson seashore and Kelana Jaya Lake using clear zone formation assay on skim milk agar medium. The extracellular protease producing bacteria identifications were based on morphological examination, Gram staining, oxidase test, lactose fermentation test, catalase test, hemolysis test and bioMérieux's API® identification system. Nine isolates, namely S1, S19, S25, L20, L21, L30, L40, L41, L44, exhibited hydrolysis capacity (HC) between 1.5 to 2.3 when incubated at 30°C for 24, 48, and 72 hour periods. The sea isolate, namely S19, exhibited the highest HC after 24, 48, and 72 h at 30ºC. S19 was identified as Bacillus cereus 2 by API 50 CHB/20E. The second-best HC was represented by lake isolate L20 and identified as Pseduomonas aeruginosa by the API 20NE system.
Keywords: API® bacterial identification system; Bacteria; Extracellular proteases; Screening